2008
DOI: 10.1121/1.2934372
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Sound Transmission Loss of Multi-layered Small Sized Elements

Abstract: In this paper an improved method for the prediction of the sound transmission loss of multilayered finite structures, like glazing will be presented. The sound transmission loss of an infinite structure is predicted with a common transfer matrix as a function of the angle of the incident sound wave. Then Villiot's spatial windowing method is applied to take into account the finiteness of the element. Usually an ideal diffuse distribution of the incident sound power is assumed and the prediction results are int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
1
0
1
Order By: Relevance
“…(34) of Davy (2009a), which is used in this paper, limits the maximum value of the limiting angle of integration to 61° in order to make the theory agree better with experimental results. Similarly, Schoenwald et al (2008) found that the spatial windowing technique was not sufficient on its own for double leaf walls and combined it with Kang's (2000) Gaussian distribution of directional incident sound energy.…”
Section: Below the Critical Frequenciesmentioning
confidence: 99%
“…(34) of Davy (2009a), which is used in this paper, limits the maximum value of the limiting angle of integration to 61° in order to make the theory agree better with experimental results. Similarly, Schoenwald et al (2008) found that the spatial windowing technique was not sufficient on its own for double leaf walls and combined it with Kang's (2000) Gaussian distribution of directional incident sound energy.…”
Section: Below the Critical Frequenciesmentioning
confidence: 99%
“…A redução sonora ao ruído aéreo de sistemas construtivos compostos pode ser largamente estimada, entretanto, ao se tratar de sistemas heterogêneos de pisos, a predição pode não ser tão simples assim (SCHOENWALD;GERRETSEN;MARTIN, 2008). Em alguns sistemas de piso são utilizados diferentes materiais de forma combinada, muitos deles leves e sem finalidade estrutural.…”
Section: Introductionunclassified